ChemInform Abstract: Al3AuIr: A New Compound in the Al—Au—Ir System. Issue 42 (October 2015) - Kadok, Joris; de Weerd, Marie‐Cecile; Boulet, Pascal; Gaudry, Emilie; Grin, Yuri; Fournee, Vincent; Ledieu, Julian
Abstract Al3AuIr is found in the Al‐rich area of the Al—Au—Ir system by arc melting and annealing of the elements in nominal composition of Al65Au20Ir15 (Ta foil in evacuated quartz tubes, 950 °C, 72 h).